Facial fabricated biocompatible homogeneous biocarriers involving biochar to enhance denitrification performance in an anoxic moving bed biofilm reactor. (December 2021) - Song, Zi; Su, Xiaoli; Li, Pu; Sun, Feiyun; Dong, Wenyi; Zhao, Zilong; Wen, Zheng; Liao, Runfeng
Graphical abstract: Highlights: Biochar combined with polyurethane sponge as new biocarrier was facially fabricated. New biocarriers enhanced simultaneously denitrification rate and efficiency in MBBR. Biochar improved biomass, bioactivity and electron transfer rate for denitrification. Abstract: Biochar prepared from pineapple peel was facially combined with polyurethane sponges for the first time to form homogeneous biocompatible biocarriers, which can enhance denitrification performance in an anoxic MBBR. The experiments showed that a higher NO3 – -N removal efficiency (96.24 ± 1.3%) and kinetic constant (0.26 h −1 ) were obtained in the MBBR employing these new biocarriers (B-MBBR), compared with a control MBBR with polyurethane sponges (C-MBBR). The attached and suspended biomass of the B-MBBR was increased by 47% and 26%, respectively. Biochar significantly enhanced the abundance of functional bacteria in terms of promoting biofilm (i.e., Leptonema ), denitrifying bacteria (i.e., Thauera, Enterobacter and Pseudomonas ) and electroactive bacteria (i.e., Geobacter ) in the B-MBBR. Meanwhile, based on the content of coenzyme I (NADH) and denitrifying enzymes, biochar would also enhance electron transport activity for denitrification. Consequently, these facial prepared biocarriers are effective to enhance denitrification performance in MBBR with application significance.